Eksplorasi Nilai Pendidikan Karakter dalam Tari Sri Ganyong: Studi di Sanggar Lang Lang Buana, Banyuwangi - Putri, Septi Riskia; Wahyuningtyas, Tri (Mahesa Research Center, 2025)
Sri Ganyong Dance is a mandatory dance at Sanggar Lang Lang Buana that incorporates cultural values related to character education. This dance has become one of the arts that represents the culture of Banyuwangi, encompassing the storyline, movements, song lyrics, makeup, and costumes. This research aims to describe the character education values found in the Sri Ganyong Dance. The research method used is descriptive qualitative. Research data were obtained through observation, interviews, and documentation from four informants. The research results show that there are 8 character education values in dance, such as religious values, honesty values, tolerance values, discipline values, independence values, hard work values, love for the homeland values, and responsibility values. These findings provide an understanding of the importance of strengthening relevant character education values in the context of local cultural preservation. As for suggestions for further research, it is recommended to provide a more detailed description of character education values in the learning process